Comparative Study of Early Secondary Nasal Revisions and Costs in Patients With Clefts Treated With and Without Nasoalveolar Molding. Issue 4 (June 2015) - Patel, Parit A.; Rubin, Marcie S.; Clouston, Sean; Lalezaradeh, Frank; Brecht, Lawrence E.; Cutting, Court B.; Shetye, Pradip R.; Warren, Stephen M.; Grayson, Barry H.
<x xml:space="preserve">Abstract</x> Abstract The present study aims to determine the risk of early secondary nasal revisions in patients with complete unilateral and bilateral cleft lip and palate (U/BCLP) treated with and without nasoalveolar molding (NAM) and examine the associated costs of care. A retrospective cohort study from 1990 to 1999 was performed comparing the risk of early secondary nasal revision surgery in patients with a CLP treated with NAM and surgery (cleft lip repair and primary surgical nasal reconstruction) versus surgery alone in a private practice and tertiary level clinic. The NAM treatment group consisted of 172 patients with UCLP and 71 patients with BCLP, whereas the non-NAM-prepared group consisted of 28 patients with UCLP and 5 with BCLP. The risk of secondary nasal revision for patients with UCLP was 3% in the NAM group and 21% in the non-NAM group. The risk of secondary nasal revision for patients with BCLP was 7% in the NAM group compared with 40% in the non-NAM group. Using multicenter averages, the non-NAM revision rates were calculated at 37.8% and 48.5% for U/BCLP, respectively. Applying these risks of revision, NAM treatment led to an estimated savings of between 491 and 4893 depending on the type of cleft. In conclusion, NAM can reduce the number of early secondary nasal revision surgeries and, therefore, reduce the overall cost of care.